2020
DOI: 10.3389/fmars.2020.578165
|View full text |Cite
|
Sign up to set email alerts
|

Marine Ecosystem Variations Over the North Pacific and Their Linkage to Large-Scale Climate Variability and Change

Abstract: In order to understand how North Pacific (NP) marine ecosystems have varied, 120 marine biological time series for both the western (29 time series) and eastern (91 time series) NP were analyzed with a Principal Component Analysis (PCA) for the period 1965-2006. This is the first attempt to conduct a multivariate analysis for a large number of marine biological data in the western and eastern NP combined. We used Monte-Carlo simulation to evaluate confidence levels of correlations and explained variance ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 65 publications
0
17
0
Order By: Relevance
“…This remarkable warming lays a foundation for the warming‐induced dynamics of LMEs. (3) Numerous studies on the Northwestern Pacific have proved the dominant roles of SST on variability in populations (e.g., Kuroda et al, 2020; Tian et al, 2013; Yatsu, 2019), communities (e.g., Ma et al, 2021; Tian et al, 2014; Tu et al, 2015), and ecosystems (e.g., Ma et al, 2020; Yati et al, 2020; Yatsu et al, 2013), which endorses the potential responses of LMEs to SST. (4) Our results provide evidence for the warming‐induced critical transitions according to Scheffer's theory (i.e., critical transition occurs at local maxima of SSTs), and the dominance shift from cold‐affinity species to warm‐affinity species also supports the driving effects of warming (also discussed in Section 4.2).…”
Section: Discussionmentioning
confidence: 99%
“…This remarkable warming lays a foundation for the warming‐induced dynamics of LMEs. (3) Numerous studies on the Northwestern Pacific have proved the dominant roles of SST on variability in populations (e.g., Kuroda et al, 2020; Tian et al, 2013; Yatsu, 2019), communities (e.g., Ma et al, 2021; Tian et al, 2014; Tu et al, 2015), and ecosystems (e.g., Ma et al, 2020; Yati et al, 2020; Yatsu et al, 2013), which endorses the potential responses of LMEs to SST. (4) Our results provide evidence for the warming‐induced critical transitions according to Scheffer's theory (i.e., critical transition occurs at local maxima of SSTs), and the dominance shift from cold‐affinity species to warm‐affinity species also supports the driving effects of warming (also discussed in Section 4.2).…”
Section: Discussionmentioning
confidence: 99%
“…A classic example is the relation between the Pacific Decadal Oscillation (PDO) and Pacific salmon catches (Mantua et al, 1997), and that between the PDO and the Japanese sardine population (Yasuda et al, 1999). A more systematic approach using principal component analysis of a large number of marine ecosystem indicators reported that many species are influenced by climate variability and change in the North Pacific and adjacent seas (Hare and Mantua, 2000 ;Tian et al, 2006;Litzow and Mueter, 2014;Ma et al, 2019;Yati et al, 2020) and in the northeast Atlantic (Brunel and Boucher, 2007). Of course, such statistical analysis can only identify correlations, which do not necessarily mean causality, and the relationships may be nonstationary.…”
Section: Biological Researchmentioning
confidence: 99%
“…The Northeast Pacific has experienced a series of environmental and species-level regime shifts (Yati et al 2020). Due to fluctuations in herring biomass during the study period (1980−2019), we wanted to test the hypothesis of different biological regimes based on SSB and surplus production (described above).…”
Section: Regime Shift Analysismentioning
confidence: 99%